Habakkuk revisited: a history friendly model of American and British technology in the nineteenth century - Roberto Fontana; Marco Guerzoni; Alessandro Nuvolari (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper presents a History Friendly Model which addresses the issue of the bifurcation in technological styles between US and Britain during the nineteenth century. The model aims at gaining a better understanding of the micro-dynamics that gave rise to different patterns of innovation in the two countries. In particular, we suggest that different demand patterns might be an explanation for the faster diffusion of capital intensive technologies in the US. Simulation results confirm this hypothesis, although only when we jointly control for the role of technological opportunities.
Keywords: O3; N0; L6; 330; Innovation; demand; history friendly model; Technologie; Innovationsdiffusion; Nachfrage; Industrieökonomik; Evolutionsökonomik; USA; Großbritannien